Design of Calcium-based Carbon Capture System for Gas-Steam Combined Cycle Assisted by Solar Thermal Tower - Lanhua LIU; Ruilin WANG; Hui HONG (发电技术)
Fossil energy power stations are the largest centralized source of CO2 emission, and the carbon emission reduction of fossil energy power stations such as coal and gas is the essential way to achieve carbon neutralization. Compared with other technologies, carbon capture based on the alkali metal has the advantages of high capture efficiency and low reaction energy consumption, but its high regeneration energy consumption will greatly affect the performance of coal-fired power stations. In this paper, a system of gas-steam combined cycle with flue gas carbon capture assisted by solar thermal tower was proposed. Taking a 467MW gas steam combined cycle power plant as the prototype, the system design and performance analysis were carried out. Compared with the original system, the power generation of the designed system was increased by 42.43MW, and the power generation efficiency reached 63%. Compared with the reference system relying on fossil energy to capture carbon dioxide, the designed power generation capacity of the system was increased by 148.5MW, and the power generation efficiency was increased by about 18 percent points. The vernal equinox day was selected as a typical day to analyze the off-design condition of the system. The results show that the system can operate at rated condition for more than six hours a day, the cumulative carbon capture capacity is 1452t, and the cumulative additional power generation is 381MW·h. The proposed system used solar energy to capture carbon dioxide without reducing the power generation efficiency of the power station itself, and realized the zero-carbon emission utilization of fossil energy. In addition, the high-temperature heat released by the calcium-based carbon capture and carbonation process was reused to the gas-steam combined cycle system for power generation to further improve the system performance. The research results can provide new ideas and methods for the multi-energy complementary and comprehensive utilization of renewable energy and fossil energy.